Floors - Carman, Patrick. (Scholastic Press, 2011)
Ten-year-old Leo's future and the fate of the extraordinary Whippet Hotel, where his father is the maintenance man, are at stake when a series of cryptic boxes leads Leo to hidden floors, strange puzzles, and unexpected alliances.